Studies on Plato, Aristotle, and Proclus : collected essays on ancient philosophy of John Cleary - Cleary, John J. (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2013)
John J. Cleary (1949-2009) was an internationally recognised authority in many aspects of ancient philosophy. As well as penetrating and original studies of Plato, Aristotle, and Proclus, he was particularly interested in the philosophy of mathematics, and ancient theories of education. The essays included in this collection display Cleary's range of expertise and originality of approach. Cleary was especially attentive to the problems involved in the interpretation of a philosophical text: in his reading of Plato he recognised the special status of dialogue as a privileged mode of philosophical writing. His underlying concern was the open-ended character of philosophy itself, to be pursued with intellectual rigour and respect both for the question and one's interlocutor. These collected essays are representative of John Cleary's philosophical life's work.